PROCESSES COUPLED TO ELECTROCOAGULATION FOR THE TREATMENT OF DISTILLERY WASTEWATERS - MEDINA COLLANA, JUAN TAUMATURGO (2024)
VINASSE IS ACIDIC, DARK BROWN WASTEWATER OBTAINED AS A RESIDUE FROM THE ALCOHOL DISTILLATION PROCESS, THE MAIN COMPONENT OF WHICH IS WATER, IN ADDITION TO MINERAL NUTRIENTS AND A HIGH ORGANIC LOAD. ELECTROCOAGULATION (EC) IS A TECHNOLOGY THAT GENERATES COAGULATING SUBSTANCES IN SITU BY OXIDIZING SACRIFICIAL ANODES THROUGH AN ELECTRIC CURRENT APPLIED TO THE ELECTRODES. DURING THE LAST DECADE, THE ELECTROCOAGULATION PROCESS HAS BEEN INTENSIVELY INVESTIGATED IN SEVERAL REVIEWS, DUE TO ITS EASE OF OPERATION, VERSATILITY, SUSTAINABILITY AND LOW ENVIRONMENTAL IMPACT. THE OBJECTIVE OF THE PRESENT WORK HAS BEEN TO MAKE A GENERAL REVIEW OF THE EC PROCESS, ITS PRINCIPLE, REACTION MECHANISM AND OPERATING PARAMETERS INVOLVED IN THE ELECTROCOAGULATION PROCESS. IN THIS RESEARCH, THE PRISMA METHOD WAS USED FOR THE ANALYSIS OF ARTICLES FROM DIFFERENT DATABASES SUCH AS SCOPUS, SCIENCEDIRECT AND GOOGLE SCHOLAR. THIS REVIEW COLLECTS NUMEROUS STUDIES OF THE EC PROCESS IN STILLAGE WASTEWATER TREATMENT AND MAKES A COMPARISON BETWEEN THESE EXPERIMENTAL RESULTS MAINLY IN TERMS OF CHEMICAL OXYGEN DEMAND REMOVAL. IN ADDITION, THIS REVIEW MAKES A COMPREHENSIVE ANALYSIS OF EC COUPLED TO OTHER PROCESSES, TAKING INTO ACCOUNT THEIR OPERATING PARAMETERS AND STILLAGE CONTAMINANT REMOVAL EFFICIENCY. THE CONCLUSION OF THIS RESEARCH POINTS OUT THAT ELECTROCOAGULATION COUPLED WITH OTHER TREATMENT PROCESSES IS VERY NECESSARY BECAUSE IT REDUCES ENERGY CONSUMPTION AND INCREASES THE RATE OF POLLUTANT REMOVAL FROM WASTEWATER. © 2024 BY THE AUTHORS.